Efektivitas Program Minat Baca pada Dinas Perpustakaan dan Kearsipan Kabupaten Balangan - Riadi, Selamat (LPPM Institut Pendidikan Nusantara Global, 2025)
This study examines the effectiveness of the Reading Interest Program at the Library and Archives Service of Balangan Regency, motivated by the low public interest in reading and the limited development of library facilities. Reading interest plays a crucial role in fostering a literate and knowledgeable society; therefore, improving library services is essential to increase community engagement. The research used a qualitative descriptive method with data collected through observation, interviews, and documentation. Ten informants were selected, consisting of library staff and community members. Data credibility was tested through prolonged observation, persistence, the use of reference materials, and member checking. The findings revealed that the program has not been fully effective. Target accuracy was moderately effective among students but less effective for the general public. Program socialization was fairly effective in terms of media use and reach, while goal achievement was still below expectations, with implementation efforts categorized as moderately effective. The main inhibiting factors include inadequate library collections, lack of digital library facilities, and declining reading interest influenced by modern technology. Supporting factors include sufficient budget allocation and staff commitment. The study concludes that the program’s effectiveness needs to be strengthened through technological innovation, such as the development of a digital library, improved cooperation with schools and communities, and enhanced promotion to build a sustainable reading culture in Balangan Regency.